Travel Motivations of Generation Y Chinese and Taiwanese Tourists Visiting Thailand: The Application of the Travel Career Pattern Approach - Wannasan, Sitanan; Jianvittayakit, Laddawan (International Journal of Multidisciplinary in Management and Tourism, 2022)
This study explores the travel motivations of Chinese and Taiwanese Gen Y tourists visiting Thailand. The concept of travel career pattern (TCP) was applied to identify the motivation patterns of these two tourist groups. Using the in-depth interview, thirty Chinese and Taiwanese Gen Y tourists disclosed their perceptions and motivations for their visit. The results reveal the differences in travel motivation and the levels of motives underpinned by the Travel Career Pattern framework. The core motives are common and crucial motivations, while the interplayed combination between the core motives and the middle-layer motives is different between the two groups. The finding offers new insights to the tourist motivation literature under the Thailand context, and illuminates tourism segmentation marketing in respect to the Chinese and Taiwanese Gen Y tourists visiting Thailand, especially during the time of the tourism recovery period.